Raising Students' Religious Sensitivity During The Covid-19 Pandemic Through Distance Islamic Education Development Program - Makruf, Syahdara Anisa; Riyanti, Erni Dewi (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2021)
Students are the intellectual generation who will perform the future social transformation. Thus, it is necessary to provide them with Islamic Education as a foundation and initial step in carrying out their role. Even though living in the Covid-19 pandemic era, students feel that the presence of muállims who intensively guide and motivate them to deepen their religious knowledge bring them a good influence. This research has two aims: to know the process of Islamic Education Development and to determine the influence of Islamic Education Development on the students' religious sensitivity. In conducting the research, the researchers employ a mixed method, i.e., qualitative, and quantitative methods. By quantitative, this research takes 168 respondents of new students of the academic year 2020/2021 who have conducted an online Islamic Education Development program during the Covid-19 pandemic. The respondents are taken with random sampling by distributing questionnaires through Google Forms. The results of the questionnaires were inputted into excel tables and processed with linear regression in SPSS 25. By qualitative, the researchers conduct naturalistic observation interviews with students and muállims. The results show a significant influence of the Islamic Education Development program (variable X) on the students' religious sensitivity (variable Y) as much as 81.7 %. In comparison, the rest, 18.3 %, are influenced by other factors outside the variable X. The Islamic Education Development program during the Covid-19 pandemic is an internalization of religious values effectively and efficiently. Besides, this internalization is a way to achieve the University of Islam Indonesia's goal, namely, to create students who will disseminate the Islamic message of Rahmatan lilálamin.